Сакральна складова феномена відкриття й освоєння перших металів - Гайко, Геннадій Іванович; Білецький, Володимир Стефанович (Український культурологічний центр, 2014)
У статті підкреслене цивілізаційне значення відкриття перших виробничих металів, розкриті передумови освоєння руд й основні етапи освоєння металів, що пов'язані з багатовіковим досвідом попередньої гірничої діяльності людства. Авторами запропонована гіпотеза народження металургії в надрах сталих спільнот архаїчних гірників, умотивованих не тільки утилітарними, але й сакральними чинниками. Нова гіпотеза розглядається в порівнянні з усталеними версіями випадкового відкриття металів.

The paper emphasizes a civilizational significance of discovery of the first production metals, covers prerequisites for ore development and milestones of mastering metals. According to the authors, inception of metallurgy was underpinned by sequential development of mining technologies of the Stone Age and related to formation of a strong cultural community of 'mining people' as early as in the Neolithic age, who had been for centuries developing non-metallic minerals and accumulating mining experience. It was within that community where purposeful long-term mastering of metals began, which was related to miners' sacral cults. The authors consider some factors of sacral and magic nature as well as activity of ministers of magic cults in the archaic miner's environment as a prerequisite for the inception of metallurgy, while admitting not only rational but also sacral practices aimed at revealing mysteries of metals (similarly to mystic practices of alchemists of historical times). Among those is the discovery of air blowing, which enabled the metal smelting process and was associated with magic rituals of ore testing with extremely strong fire, i.e. the high-temperature mode could have been initially developed on the basis of 'ideological' rather than 'technological' motivation. Achievements of archaeometallurgy of the recent decades offer brand new evidence to the present-day vision of the Neolithic revolution development, allow to identify an individual well-established community of miners metallurgists and bring it into line with communities of crop growers and breeders as an important constituent of the Neolithic revolution progress.
Sacral constituent of the phenomenon of first metals discovery and mastering
Keywords: історія гірництва; виробнича археологія; народження металургії; первісні гірничі спільноти; сакральні фактори; гірничі культи; ірраціональні традиції; history of mining; production archeology; inception of metallurgy; primary mining communities; sacral factors; mining cults; irrational traditions